(untitled) (LEARNing Landscapes, 2011)
In this article, the author shares new approaches to data collection and analysis which encourage using "crystallization": an intriguing new method that has emerged in recent years as a kind of three-dimensional data analysis strategy that welcomes the new lens that artistic thinking can bring to conducting and writing research. Examples from teacher-researchers include ways to use storytelling, art, self-reflection, children’s books, metaphor, and imagination to expand the field of data collection and analysis.